Rekonstrukcii Christa v rabotach Julii Latyninoj = Reconstruction of Christ in the works of Yulia Latynina - Lichošerstov, Aleksandr (Bogoslovs'ki rozdymi, 2020)
Khristos s tysiachiu lits [Christ with a Thousand Faces]. Iuliia Latynina.Moscow: "Eksmo", 2019. 503 p. ISBN 9785041015442;270.00 UAH .